Direct evidence for income comparisons and subjective well-being across reference groups - Laszlo Goerke; Markus Pannenberg (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2015)
This note provides evidence for the relationship between income comparisons and subjective well-being (SWB), using novel German data on self-reported comparison intensity and perceived relative income for seven reference groups. We find negative correlations between comparison intensity and SWB for colleagues, people in the same occupation and friends, but not for other reference groups, such as neighbours. Work-related income comparisons are mostly upwards and there is a strong negative correlation between perceiving to earn less than the reference group and SWB.
Keywords: D31; D62; I31; 330; Income Comparisons; German Socio-Economic Panel (SOEP); Relative Income; Subjective Well-Being